A chiral polycyclic aromatic hydrocarbon monkey saddle - Kirschbaum, Tobias; Rominger, Frank; Mastalerz, Michael (Angewandte Chemie. International edition, 2020)
A contorted polycyclic aromatic hydrocarbon (PAH) in the shape of a monkey saddle has been synthesized in three steps from a readily available truxene precursor. The monkey saddle PAH is consisting of three five-, seven six-, and three eight-membered rings and has been unambiguously characterized by single-crystal X-ray diffraction. Owing to the three biaryl axes the monkey saddle PAH is inherently chiral. The inversion of the two enantiomeric structures into each other preferably occurs through a twisting of peripheral rings rather than by a fully planar intermediate, as has been calculated by DFT methods. Enantiomers were separated by chiral HPLC and inversion barriers determined by variable temperature circular dichroism spectroscopy, supporting the twisting mechanism.